Prevalence of Pulmonary Tuberculosis among Rohingya Refugees in Kutupalong Camp, Bangladesh - Jasmine, Rezina; Khan, Arif Ahmed; Kamal, AHM Kazi Mostofa; Karim, ATM Rezaul; Haque, Md Monirul (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: An estimated over seventy thousands Rohingya refugees living in Bangladesh since August 2017. World Health Organization (WHO) warned that there could be an outbreak of infectious diseases like tuberculosis (TB) among the Rohingya that would also be a threat to the local people. Objectives: To find out the prevalence of TB among Rohingya refugees in Kutupalong camp, Ukhiya. Materials and Methods: This cross-sectional observational study was conducted at the field medical laboratory of Bangladesh Army in the refugee camp Kutupalong, Ukhiya from September to December, 2017. Total 3579 patients reported during this time thosehad cough for more than 2 weeks were selected as study subjects. The Ziehl Neelsen stained smears were prepared from the sputum samples and examined only under microscope for acid fact bacilli (AFB). All AFB positive cases were tested by molecular technique, Genexpert for drug resistance and screened by immunochromatographic test(ICT) for HIV. Results: Out of 3579 reported cases 55(1.54%) were AFB positive. Among 55 positive cases 27(49.09%) were female and 28(50.90%) were male.There was no HIV casefound among 55 AFB positive patients but 01 case was found positive as multi drug resistant TB (MDR-TB). Conclusion: This study showed prevalence of TB is quite high in Rohingya population due to malnutrition, unhealthy living condition and general lack of awareness. Directly Observed Treatment Short Course (DOTS) had already started to eradicate TB which will definitely prevent contagiousness to local people in Bangladesh. Journal of Armed Forces Medical College Bangladesh Vol.14 (2) 2018: 197-199